Actinobacillus pleuropneumoniae cytotoxins on size, granularity and viability of porcine neutrophils - Simson Tarigan (Indonesian Center for Animal Research and Development (ICARD), 1998)
Cytotoxins produced by Actinobacillus pleuropneumoniae are supposed to play major roles in bacterial pathogenicity and virulence. To gain better understanding in the mechanism of the pathogenicity, cytotoxic activities of the toxins on porcine neutrophils were investigated in vitro. Changes in cell size, granularity and viability were examined with a flow cytometer. Cell size and granularity correlate with forward light scatter and right angle light scatter, respectively; whereas, cell viability corresponds with fluorescent intensity of cells stained with propidium iodide . At low concentrations (dilutions between 1/10 and 1/100 of bacterial culture supernatants), the cytotoxins induced severe swelling and degranulation of neutrophils; whereas, at higher concentrations (dilutions of 51/10 bacterial culture supernatants), the cytotoxins caused rapid cell death. There was no significant difference in cytotoxic activities of Cyooxins derived from various serotypes (serotypes 1, 2, 3, 5 and 7 ) of A. pleuropneumoniae . Morphologically, the cytotoxin-treated neutrophils stained with Giemsa showed profound changes. Neutrophils treated with low dosages of Cyooxins became swollen with spherical nuclei . Higher concentration of cytotoxins study indicates strongly that important mechanism in the caused vactiolation of cytoplasts, enlargement or disintegration of nuclei . This in vitro intoxication of neutrophils by cytotoxins produced by A. pleuropneumoniae comprises anpathogenicity of the bacteria. Key words : Actitiobacilluspleuropneumoniae, cytotoxin, neutrophils, pig, flow cytometry